The Effect of Health Education and Mobile Control Application Program on Anemia among Pregnant Women - Rukmaini ,; Nur Indrawaty Lipoeto ,; Masrul ,; Nursyirwan Effendi, (Journal of Pharmacy and Nutrition Sciences, 2019)
Background: anemia is one of the most widespread nutritional deficiency diseases. An intervention is needed to improve Hb among pregnant women in order to avoid maternal and perinatal complication and deaths. The use of mobile control application has improved the compliance of ferrum tablet consumption. This study aimed to assess the effect of health education and mobile application control on anemia among pregnant women. Methodology: The design of t he res earc h is quasy experimental. The study was conducted in Banten from September to December 2017. Multistage cluster sampling technique was used in this research. The samples were divided into experimental and control groups. The experimental group consists of health education using a module and the mobile application program. The data were analyzed using descriptive and inferential statistics. Wilcoxon sign rank test and independent t-test were used with alpha .05. Results: There was a significant difference of pregnant women’s knowledge (z= -7.187, p= .005), pregnant women’s perception (z= -7.054, p= .005), and pregnant women attitude before and after intervention (z= -6.35, p= .005). There was a significant difference of family knowledge (z= -6.53, p= .005), family attitude (z= -4.56, p= .005), and family support before and after intervention (z= -7.08, p= .005). There was a difference of Hb mean between experiment and control group after the intervention (t= 7.12, p= .005). Conclusions: health education and mobile control application program has a positive effect on anemia among pregnant women. An advocacy is required at governmental level after developing a frame of reference for understanding anemia in pregnancy.